Sebuah Kemandirian Industri Pertahanan Indonesia dan Tantangannya Alokasi Anggaran Pertahanan - Surahman, Surahman; I Nengah Putra; Khaerudin , Khaerudin; Muhamad Asvial (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research aims to explore key issues related to Indonesia's economic potential, particularly its Gross Domestic Product (GDP) reaching US$9.3 trillion. The International Monetary Fund (IMF) projections indicate that by 2030, Indonesia will be one of the top economic powers, competing with India and Brazil. The primary focus of the research is the defense sector as a strategic potential requiring a proactive response. The research objectives involve exploring the level of self-sufficiency in the defense industry, understanding challenges related to defense budget allocation, and identifying factors influencing global competitiveness. The research methodology is descriptive with a qualitative document-based approach, specifically focusing on strategic State-Owned Enterprises (SOEs) within Defense ID, such as PT Len, PT Pindad, PT PAL, PT DI, and PT Dahana. Data analysis encompasses information from these SOEs, utilizing theoretical frameworks including Competitive Theory, Penta-Helix Theory, Defense Industry Cluster Concept, and Central Government Budgeting Model. Research findings indicate that SOEs within Defense ID can be considered self-sufficient in the global defense industry competitiveness. However, it is noteworthy that the Defense Budget allocation is still below 1% of the GDP, creating its own challenges. The conclusion of the research is that Indonesia has significant potential to develop a self-reliant defense industry capable of global competition. Recommendations include enhancing collaboration, developing Pentahelix or Septahelix concepts, and implementing Defense Industry Clustering to improve innovation, efficiency, and competitiveness in the sector. Additionally, the Defense Budget Allocation Policy significantly influences the progress of this industry, requiring proactive measures to ensure alignment with the desired economic growth. Thus, the research findings provide a foundation for the Government, Stakeholders, and Future Researchers to develop strategies and policies supporting optimal growth in the Indonesian Defense sector.